Literacy and Disabilities in Education : How Involved Are We? (A Systematic Literature Review) - Husamah, H.; Rahardjanto, Abdulkadir; Ekowati, Dyah Worowirastri; Luzyawati, Lesy; Adlini, Miza Nina (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to review, investigate, and compare various research published in Scopus-indexed journals related to the theme of literacy for disabilities so that it will contribute to the development of literacy studies for disability groups. This study used the systematic literature review method with the PRISMA 2020 model. The search was conducted in the Scopus database, inclusion-exclusion, to obtain 41 articles. Data were collected from the Scopus database tend to increase in 2019-2023. Data were analyzed using thematic analysis techniques. The study results showed that this theme (literacy and disability) has broad dimensions and involves all parties. Various aspects of literacy can be promoted for people with disabilities, although there are adjustments. Ahlgrim-Delzell is the dominant researcher, the reference, and the pivot. The disability aspect was related to education, children, and young adults. Interestingly, the theme "literacy and disabilities" is the focus of researchers from all continents and is generally written in groups. Although this theme deserves global attention, it is not yet interesting for international cooperation. We discuss all aspects of the trend. Researcher interest continues to increase regarding "literacy and disabilities," which can be seen based on distribution year, research types/methods, instruments, study aspects, author, keywords, author’s nationality, and collaboration.